Blended learning : research perspectives - Picciano, Anthony G.; Dziuban, Charles; Graham, Charles R. (London : Routledge, Taylor & Francis Group, 2014)
'Blended learning, which combines the strength of face-to-face and technology-enhanced learning, is increasingly being seen as one of the most important vehicles for education reform today. Blended learning allows both teacher and learner access to radically increased possibilities for understanding how we transmit and receive information, how we interact with others in educational settings, how we build knowledge, and how we assess what we have taught or learned. Blended Learning: Research Perspectives, Volume 2 provides readers with the most current, in-depth collection of research perspectives on this vital subject, addressing institutional issues, design and adoption issues, and learning issues, as well as an informed meditation on future trends and research in the field. As governments, foundations, schools, and colleges move forward with plans and investments for vast increases in blended learning environments, a new examination of the existing research on the topic is essential reading for all those involved in this educational transformation.'--
Introduction to blended learning : research perspectives, volume 2 / Anthony Picciano -- Blended learning models and scale. Developing models and theory for blended learning research / Charles R. Graham, Curtis R. Henrie, and Andrew S. Gibbons -- Scaling blended learning evaluation beyond the university / Patsy D. Moskal and Thomas B. Cavanagh -- Investigating informal blending at the University of Illinois Springfield / William Bloemer and Karen Swan -- Evaluation. SCOPe-ing out interactions in blended environments / Susan J. Wegmann and Kelvin Thompson -- Student perspectives on blended learning through the lens of social, teaching, and cognitive presence / Janelle DeCarrico Voegele -- To be or not to be : student and faculty perceptions of engagement in a blended bachelor of education program / Norman Vaughan, Allana LeBlanc, Jim Zimmer, Irene Naested, Jodi Nickel, Stefan Sikora, Gladys Sterenberg, and Kevin O'Connor -- A five-year study of sustaining blended learning initiatives to enhance academic engagement in computer and information sciences campus courses / Laurie P. Dringus and Amon B. Seagull -- Trial and error : iteratively improving research on blended learning / D. Christopher Brooks and Jodi R. Sandfort -- Practice makes perfect? : assessing the effectiveness of online practice exams in blended learning biology classes / J.D. Walker, D. Christopher Brooks, Kyle Hammond, Bruce A. Fall, Richard W. Peifer, Rogene Schnell, and Janet L. Schottel -- Faculty issues. Implementation of blended learning for the improvement of student learning / Jeannette E. Riley, Catherine Gardner, Sarah Cosgrove, Neal Olitsky, Caitlin O'Neil, and Chan Du -- The impact of instructional development and training for blended teaching on course effectiveness / Tanya M. Joosten, Dylan Barth, Lindsey Harness, and Nicole L. Weber -- Growing your own blended faculty : a review of current faculty development practices in traditional, not-for-profit higher education institutions / Amy P. Ginsberg and Elizabeth Ciabocchi -- Choice does matter : faculty lessons learned teaching adults in a blended program / Karen Skibba -- Studying non-traditional learners. Variation in adult learners' experiences of blended learning in higher education / Paige L. McDonald -- Educating warrior diplomats : blended and unconventional learning for special operations forces / Katherine M. Tyler and Kent C. Dolasky -- International perspectives.'Are you working in the kitchen?' : European perspectives on blended learning / Anders Norberg and Isa Jahnke -- Out of hours : online and blended learning workload in Australian universities / Yoni Ryan, Belinda Tynan, and Andrea Lamont-Mills -- Blended learning in K-12 environments. Blended learning in the K-12 education sector / Heather Staker and Michael B. Horn -- Blended learning in New York City : the iLearnNYC program / Anne-Marie Hoxie, Jennifer Stillman, and Kara Chesal -- Blending it all together / Charles D. Dziuban, Joel L. Hartman, and George L. Mehaffy.
Includes bibliographical references and index.
Keywords: Blended learning; Blended learning